1988
DOI: 10.1164/ajrccm/137.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cyclooxygenase and Lipoxygenase Mediators in Oxidant-induced Lung Injury

Abstract: Infusion of the oxidant lipid peroxide tert-butyl hydroperoxide (t-bu-OOH) causes pulmonary vasoconstriction and increases vascular permeability in isolated perfused rabbit lungs. We have previously shown that t-bu-OOH stimulates arachidonic acid metabolism, increasing the synthesis of the cyclooxygenase products. The current experiments were designed to determine the role that cyclooxygenase- and lipoxygenase-derived mediators play in the lung injury caused by t-bu-OOH. In the present experiments, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Ischemia was continued for 60 min, during which lungs were ventilated with 5% CO2 in air, followed by reperfusion at 12 ml/min for 3 min. This regimen for indomethacin treatment essentially abolished production ofthromboxane B2 assayed in the lung homogenate and perfusion medium with a radioimmunoassay kit (Amersham Corp., Arlington Heights, IL) (data not shown) consistent with previous results of others with perfused rabbit lungs (19). Ischemia produced a significant increase in TBARS in ischemic lungs even in the presence of indomethacin.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Ischemia was continued for 60 min, during which lungs were ventilated with 5% CO2 in air, followed by reperfusion at 12 ml/min for 3 min. This regimen for indomethacin treatment essentially abolished production ofthromboxane B2 assayed in the lung homogenate and perfusion medium with a radioimmunoassay kit (Amersham Corp., Arlington Heights, IL) (data not shown) consistent with previous results of others with perfused rabbit lungs (19). Ischemia produced a significant increase in TBARS in ischemic lungs even in the presence of indomethacin.…”
Section: Resultssupporting
confidence: 89%
“…The increase in lipid peroxidation products could represent either the generation of eicosanoids from arachidonic acid or the less specific peroxidation of membrane or other tissue lipids. Based on studies with inhibitors of the cyclooxygenase and lipoxygenase pathways, -40-50% of the increase in lipid peroxidation products in this study was related to activation of eicosanoid metabolism by ischemia, compatible with previous reports of increased eicosanoid production during oxidative injury (19). Conversely, more than half ofthe lipid peroxidation products presumably arose from attack on tissue lipids.…”
Section: Discussionsupporting
confidence: 89%
“…Results from this study and previous ones do not indicate that elevated PUFA work through accentuating the development of the pulmonary antioxidant enzymes or surfactant production, nor through enhancing the ability of the newborn animal to mount a protective increase in pulmonary antioxidant enzymes in response to hyperoxic exposure. Other investigators have suggested a role for lung eicosanoids in the development of (or protection from) oxygen toxicity (22)(23)(24)(25). In our present study, we were unable to demonstrate differences in PGE2, 6-keto-PGF,-a (the metabolite of prostacyclin), or in the LTC4-F4 in lung tissue of either diet group either in air or hyperoxia ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of rabbits with the hemolytic agent, phenylhydrazine [162], or hemorrhagic events [163] cause a > 1000-fold rise in 15-LO levels in heart, lung, and aorta. An infusion of the oxidant tert-butyl hydroperoxide in isolated rabbit lung elevates LTB 4 , C 4 , D 4 , and E 4 content by two-to three-fold [164]. A significant rise in 15-HETE occurs when human bronchial epithelial cells are exposed in vitro to toluene di-isocyanate [165].…”
Section: Modulation Of Lipoxygenase Activitymentioning
confidence: 92%